Spatialising African indigenous customs in Langa - Molefe, Rampedi Lesego (School of Architecture, Planning and Geomatics, 2016)
1.1 Background African Traditional Customs form an important part in the lives of millions of people on the African continent. They are the thread that stitches together the multifaceted blanket of African cultural variety. 1.2 Issue The problem is that of designing an African city that is representative of the cultural fabric and diversity in its spatial structuring and order. Although a city like Cape Town is considered an 'African city' it fails to spatially accommodate African customs that are the core ingredients of being African. Historically African lifestyle values found resistance in expression and loss of meaning within an urban context. The city in its conception and planning does not adequately address the need for African customs that find expression in the more rural context. Now that South Africa is emancipated from the bonds of apartheid, a new era of redefining African Identity has come. The question of African identity cannot be ignored because it is fundamental to solving many societal problems that develop from a loss of character personally and collectively. Many black South Africans living in Cape Town do not consider the city as their 'home'. The majority are of Xhosa lineage and do not feel that their lives are not well rooted in the urban environment. Many still consider the Eastern Cape 'ekhaya' (home), because that is where generations of amaXhosa set their roots. Even though some amaXhosa were raised as second and third generation inhabitants in Cape Town, the stronghold of their traditional roots is evident in their attitude towards their ancestral home. It is marked by the annual pilgrimage to the Eastern Cape by thousands of people who return home to fulfil traditional rituals and customs. For those growing up in Cape Town without a strong family ties or cultural roots with the Eastern Cape, their sense of identity is often lacking because the pillar of traditional ritual is absent in their lives. Personally I believe that a person's self-worth is directly related to their spiritual constitution, and that African traditional customs are not only important but they need to find expression in the environments that people live in daily. 1.3 Design Question How can African Traditional Customs be accommodated in the urban setting by physically finding expression and relevance practically and spatially. 1.4 The Site This project is located in Langa township because of the history of African people who have lived in the urban setting while upholding their traditional practices.